Higher Education 4.0: capturing the voices of faculty members - Shal, Tarek; Ghamrawi, Norma; Abu-Tineh, Abdullah; Alshaboul, Yousef (Frontiers in Education, 2026)
IntroductionEducation 4.0 is rapidly reshaping higher education through technology-enabled learning, curriculum realignment, and new ethical and professional demands. However, empirical evidence on how faculty members in the Arab States perceive and respond to these shifts remains limited.MethodsThis qualitative study examined faculty sense-making of Education 4.0 through semi-structured interviews with 12 university faculty members from six Arab countries. Data were analysed using thematic analysis.ResultsParticipants conceptualised Education 4.0 as (a) strengthening curriculum relevance through closer alignment with labour-market needs, (b) widening access to knowledge through digital resources and networks, and (c) enabling more differentiated, student-centred pedagogy. Concurrently, they highlighted persistent challenges related to ethical governance, uneven institutional and individual readiness, and the necessity of continuous, context-responsive professional development.DiscussionBy foregrounding faculty perspectives across multiple national contexts, the study illuminates the opportunities and tensions shaping Higher Education 4.0 implementation in the Arab States and underscores the importance of supporting human-centred, ethically governed digital transformation.